Philopatry at the frontier: A demographically driven scenario for the evolution of multilevel societies in baboons (Papio). Issue 146 (September 2020) - Jolly, Clifford J.
Abstract: The baboons ( Papio sp.) exhibit marked interspecies variation in social behavior. The thesis presented here argues, first, that male philopatry is a crucial factor, arguably the crucial factor, underlying the other distinctive features (one-male units, multilevel society) shared by hamadryas and Guinea baboons, but not other species of Papio . The second suggestion is that male philopatry as a population norm was not an adaptation to a particular habitat or set of ecological circumstances but evolved in the common ancestor of hamadryas and Guinea baboons as a response to natural selection in the demographic context peculiar to the frontier of a rapidly expanding population. Other derived features of social structure (male-male tolerance, some facultative female dispersal) subsequently evolved to accommodate male philopatry. The mitochondrial genetic population structure of extant baboons preserves a footprint of the initial expansion of 'modern' Papio . Immediately after the expansion, male-philopatric, multilevel populations with a general physical and behavioral resemblance to Guinea baboons occupied the whole northern hemisphere range of the genus. Behavioral and physical autapomorphies of hamadryas baboons evolved in a subpopulation of this ancestral northern base, in response to a less productive habitat of the Horn of Africa. Subsequently, ancestral olive baboons 'reinvented' male dispersal. They and yellow baboons, another male-dispersing species, then replaced most of the male-philopatric northern populations, by male-driven introgression and nuclear swamping.